2021
DOI: 10.1371/journal.pone.0253702
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathologic significance of Tks5 expression of peritoneal mesothelial cells in gastric cancer patients

Abstract: Background Gastric cancer (GC) patients frequently develop peritoneal metastasis. Recently, it has been reported that peritoneal mesothelial cells (PMCs) activated by GC cells acquire a migratory capacity and promote GC cell invasion. The invasiveness of PMCs reportedly depends on the activity of Tks5, an adaptor protein required for invadopodia formation. However, the relationship between clinicopathologic features and Tks5 expression in PMCs has been poorly documented. In this study, we evaluated the clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…79 The 3-year peritoneal recurrence-free survival rate was significantly lower in patients with TKS5-positive than TKS5-negative PMCs, but was not affected by Tks5 expression in cancer cells, indicating that Tks5 expression in PMCs may be a useful predictive marker of peritoneal recurrence in gastric cancer patients. 79 In addition to their roles in peritoneal metastasis, MCs also promote cancer chemoresistance and stemness. Ovarian cancer cells were found to induce osteopontin expression and secretion by MCs through TGF-β signaling.…”
Section: Roles Of Mc-derived Cafs (Mc-cafs) In Cancer Progression Mc-...mentioning
confidence: 83%
See 1 more Smart Citation
“…79 The 3-year peritoneal recurrence-free survival rate was significantly lower in patients with TKS5-positive than TKS5-negative PMCs, but was not affected by Tks5 expression in cancer cells, indicating that Tks5 expression in PMCs may be a useful predictive marker of peritoneal recurrence in gastric cancer patients. 79 In addition to their roles in peritoneal metastasis, MCs also promote cancer chemoresistance and stemness. Ovarian cancer cells were found to induce osteopontin expression and secretion by MCs through TGF-β signaling.…”
Section: Roles Of Mc-derived Cafs (Mc-cafs) In Cancer Progression Mc-...mentioning
confidence: 83%
“…Immunohistochemistry has shown that TKS5 is expressed by around 65% of PMCs from the omentum and retroperitoneum of gastric cancer patients who underwent gastrectomy 79 . The 3‐year peritoneal recurrence‐free survival rate was significantly lower in patients with TKS5‐positive than TKS5‐negative PMCs, but was not affected by Tks5 expression in cancer cells, indicating that Tks5 expression in PMCs may be a useful predictive marker of peritoneal recurrence in gastric cancer patients 79 …”
Section: Roles Of Mc‐derived Cafs (Mc‐cafs) In Cancer Progressionmentioning
confidence: 99%
“…Mesothelial cells have been demonstrated to progressively acquire features of CAFs. 62 CAFs driven through TGF-b signaling pathways sustain and stimulate tumor proliferation. RHBDF2 expressed by CAFs is induced by inflammatory cytokines present in the malignant ascites and secreted by tumor cells.…”
Section: Mesothelial Mesenchymal Transitionmentioning
confidence: 99%